Analysis of Interaction Patterns Among Deaf Students Through The Peer Tutor Method in Mathematics Learning - Verjunnea Ali Choiriyan; Fadhilah Rahmawati; Nina Agustyaningrum (Universitas Wiralodra, 2026)
Deaf students have characteristics of learning mathematics that are highly dependent on visual channels due to limited linguistic and sensory access, so that abstract mathematics learning often becomes a challenge. The mismatch between these characteristics and teachers' delivery of material that is predominantly verbal or uses complex language structures results in less effective learning communication. This study aims to gain an in-depth understanding of the patterns and dynamics of interaction among deaf students during the application of the peer tutoring method in mathematics learning, particularly in flat geometry. The research used a qualitative approach with a case study design involving 16 deaf students at SLB-B YPPALB Magelang City from elementary to high school levels, divided into four heterogeneous groups based on the level of hearing impairment, additional disabilities, and peer tutor roles. Data were collected through structured classroom observation, learning documentation, and semi-structured interviews, then analyzed through data reduction, data presentation, and conclusion drawing stages. The results showed that interactions between students through peer tutors were more intensive and effective than interactions between students and teachers. These findings are in line with Vygotsky's Social Constructivism theory, which emphasizes the role of social interaction and peer scaffolding in learning. Peer tutors function as linguistic and social mediators through sign language, gestures, and concrete representations, thereby facilitating the understanding of mathematical concepts. The dynamics of interaction are influenced by the degree of hearing loss, additional disabilities, and the communication skills of peer tutors. These findings recommend that mathematics learning for deaf students be strategically designed based on peer tutoring to improve interaction, participation, and conceptual understanding.